2001
DOI: 10.2140/pjm.2001.200.43
|View full text |Cite
|
Sign up to set email alerts
|

Alexander and Thurston norms of fibered 3-manifolds

Abstract: For a 3-manifold M , McMullen derived from the Alexander polynomial of M a norm on H 1 (M, R) called the Alexander norm. He showed that the Thurston norm is an upper bound for the Alexander norm. He asked if these two norms were the same when M fibers over the circle. Here, I give examples that show this is not the case. This question relates to the faithfulness of the Gassner representations of the braid groups. The key tool used is the Bieri-Neumann-Strebel invariant, and I show a connection between this inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…When the class φ represents a fibration, this bound becomes an equality, and ∆ N has peculiar properties, as shown from the following theorem, implicitly or explicitly proven, with different techniques, in [Du01], [McM02], [Vi03], and [FK06]. Remember that Thurston [Th86] showed that if a class φ ∈ H 1 (N ) is fibered then it lies in the cone over some topdimensional face F T .…”
Section: Symplectic Products and The Ordinary Alexander Polynomialmentioning
confidence: 99%
“…When the class φ represents a fibration, this bound becomes an equality, and ∆ N has peculiar properties, as shown from the following theorem, implicitly or explicitly proven, with different techniques, in [Du01], [McM02], [Vi03], and [FK06]. Remember that Thurston [Th86] showed that if a class φ ∈ H 1 (N ) is fibered then it lies in the cone over some topdimensional face F T .…”
Section: Symplectic Products and The Ordinary Alexander Polynomialmentioning
confidence: 99%
“…In many cases it is easier to find representations ofM . This approach allows us to determine the Thurston norm ball of Dunfield's link [Du01] (see Section 5.2).…”
Section: Theorem 32 (Main Theorem 2) Let M Be a 3-manifold With B 1mentioning
confidence: 99%
“…Theorem 5.7 easily gives A simple example is shown in Figure 13. The BNS picture can also be connected to the Alexander polynomial, in particular to the coefficients which occur at the vertices of the Newton polygon [9].…”
Section: Propositionmentioning
confidence: 99%